A Comprehensive Study of Osteogenic Calcium Phosphate Silicate Cement: Material Characterization and In Vitro/In Vivo Testing. Issue 4 (16th December 2015) - Gong, Tianxing; Wang, Zhiqin; Zhang, Yixi; Zhang, Yubiao; Hou, Mingxiao; Liu, Xinwei; Wang, Yu; Zhao, Lejun; Ruse, N. Dorin; Troczynski, Tom; Häfeli, Urs O.
Abstract : Vertebral compression fractures can be successfully restored by injectable bone cements. Here the as‐yet unexplored in vitro cytotoxicity, in vivo biodegradation, and osteoconductivity of a new calcium phosphate silicate cements (CPSC) are studied, where monocalcium phosphate (MCP; 5, 10, and 15 wt%) is added to calcium silicate cement (CSC). Setting rate and compressive strength of CPSC decrease with the addition of MCP. The crystallinity, microstructure, and porosity of hardened CPSC are evaluated by X‐ray diffractometer, Fourier transform infrared spectroscopy, and microcomputed tomography (CT). It is found that MCP reacts with calcium hydroxide, one of CSC hydration products, to precipitate apatite. While the reaction accelerates the hydration of CSC, the formation of calcium silicate hydrate gel is disturbed and highly porous microstructures form, resulting in weaker compressive strength. In vitro studies demonstrate that CPSC is noncytotoxic to osteoblast cells and promotes their proliferation. In the rabbit tibia implantation model, clinical X‐ray and CT scans demonstrate that CPSC biodegrades slower and osseointegrates better than clinically used calcium phosphate cement (CPC). Histological studies demonstrate that CPSC is osteoconductive and induces higher bone formation than CPC, a finding that might warrant future clinical studies. Abstract : Monocalcium phosphate‐added calcium phosphate silicate cement's biocompatibility, biodegradation, and osteoconductivity are studied in this research. It is found that this particular bone cement is biocompatible and promotes osteoblast proliferation. In addition, it demonstrates slower biodegradation and better osseointegration than clinically used calcium phosphate cement.